Layanan Mobile Banking dalam Mewujudkan Kepuasan Nasabah BSI di Surabaya - Febri Rahmah; Sutono Sutono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the quality of Bank Syariah Indonesia (BSI Mobile) mobile banking services in providing customer satisfaction at Bank Syariah Indonesia KCP Diponegoro 2 Surabaya. The research method uses a quantitative approach. The population in this research is all BSI KCP Diponegoro 2 Surabaya customers. Meanwhile, the sample in this research is some BSI KCP Diponegoro 2 Surabaya customers who use the BSI Mobile application. Considering the large population so that the exact number cannot be known and the limited time in conducting research, this research uses the Lemeshow formula with a maximum estimate of 7% and an error rate of 5% as a guideline in finding the number of samples used. So through this technique a sample of 100 respondents was obtained. Data was collected through distributing questionnaires using incidental sampling technique. The data analysis process uses simple linear regression, hypothesis testing, and coefficient of determination. The research results show that the quality of BSI Mobile services has an influence on customer satisfaction. The influence between the independent variable and the dependent variable is 79.2%, while 20.8% is influenced by other factors not included in this research. This research can help increase customer satisfaction in using the BSI Mobile application.